Bibliometric analysis of research trends in rigid pavement over the last decade - Mudjanarko, Sri Wiwoho; Paikun, Paikun; Daniel, Basil David (Universitas Mercu Buana, 2025)
This study presents a bibliometric analysis of research trends in rigid pavement over the last decade, aiming to identify publication trends, research output distribution, main themes, citation patterns, and research gaps. The PRISMA method was employed, and statistical analysis was conducted using bibliometric software. By collecting bibliographic data from academic publications, this research reveals a significant growth in rigid pavement publications, reflecting increased global interest in this field. Major research themes include pavement design, material characterization, construction techniques, maintenance, and performance evaluation. Citation pattern analysis is used to identify influential works in this field. However, this study has limitations in data coverage and is susceptible to biases inherent in bibliometric analysis. Nevertheless, it contributes significantly to understanding the research landscape of rigid pavement, providing valuable insights for researchers, practitioners, and policymakers. Future research could deepen qualitative analysis, track the evolution of research themes, and explore interdisciplinary frameworks to enrich our understanding of rigid pavements.